Hubungan Tingkat Stress, Aktivitas Fisik, Konsumsi Makanan Tinggi Natrium Dan Tekanan Darah Pada Lansia (55-64 Tahun) Di UPTD Puskesmas Jatiasih Kota Bekasi - Hanifah Reviana Hartono; Idrus Jus’at; Anugrah Novianti; Harna Harna; Yulia Wahyuni (Jurnal Medika Nusantara, 2023)
Background: Blood pressure is the heart's ability to contract like a pump in pushing blood to continue to flow throughout the body in the blood vessels. Risk factors caused high blood pressure can be divided into two uncontrolled factors such as gender, age and family history. While the controlled factors include stress levels, physical activity, obesity, and high-sodium foods consumption. Objective: This study was to determine the correlation between stress levels, physical activity, consumption of high-sodium foods and blood pressure in the elderly (55-64 years) at UPTD Puskesmas Jatiasih, Bekasi City. Research Methods: This research is a cross-sectional approach, with data analysis used is the chi-square statistical test. The research sample was taken using the calculation method using G*power. The population in this study were the elderly (55-64 years) at the UPTD Jatiasih Health Center, Bekasi City, with a total of 46 subjects. DASS 21 stress level instrument, PASE physical activity, consumption of foods high in sodium Semi-FFQ. Result: of the study that Correlation between high sodium food consumption and systolic blood pressure p value = 0,001, correlation between high sodium food consumption and diastolic blood pressure p value = 0,823, stress level correlation with systolic blood pressure p value = 0,095, stress level correlation with diastolic blood pressure p value = 0,573, physical activity correlation with systolic blood pressure p value = 0,328, physical activity correlation with diastolic blood preassure p value = 0,345. Conclusion: from the result of the analysis of high sodium food consumtion, there is a signicant correlation between high sodium food consumption and systolic blood pressure in the elderly with a p value = 0,001 (p<0,05) at the UPTD Puskesmas Jatiasih, Bekasi City.